2023
DOI: 10.3389/fgwh.2023.1153640
|View full text |Cite
|
Sign up to set email alerts
|

Level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia: a systematic review and meta-analysis

Fantu Mamo Aragaw,
Daniel Gashaneh Belay,
Mastewal Endalew
et al.

Abstract: BackgroundEpisiotomy at the time of vaginal birth is a common lifesaving surgical procedure. In Ethiopia, several studies have been conducted concerning the proportion of episiotomy. However, its prevalence varies across these series of studies. Thus, this systematic review and meta-analysis aimed to estimate the level of episiotomy practice and its disparity among primiparous and multiparous women in Ethiopia.MethodsThis systematic review was reported according to the Preferred Reporting Items for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
1
0
1
Order By: Relevance
“…A multicenter clinical trial conducted in 2019 observed a 10% rate of perineal intactness in multiparous women, emphasizing the need for a restrictive episiotomy approach to childbirth to reduce perineal trauma. These findings were consistent with several studies in which primiparity was identified as one of the main risk factors associated with episiotomy [21][22][23][24][25][26]. In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A multicenter clinical trial conducted in 2019 observed a 10% rate of perineal intactness in multiparous women, emphasizing the need for a restrictive episiotomy approach to childbirth to reduce perineal trauma. These findings were consistent with several studies in which primiparity was identified as one of the main risk factors associated with episiotomy [21][22][23][24][25][26]. In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, factors such as fetal weight greater than 4000 g and vacuum extraction have been found to be independent risk factors for both second-degree perineal tears and obstetric anal sphincter injury [21]. Other studies have also identified influential factors for the performance of episiotomy in primiparous women, such as maternal age, maternal body mass index, presence of analgesia, duration of the second stage, estimated birth weight, and perineal stress [22][23][24][25][26]. These findings led us to ask what characteristics are determinant for a higher rate of episiotomy in primiparous women and whether these characteristics justify the difference in numbers compared to multiparous women.…”
Section: Discussionmentioning
confidence: 99%
“…De manera similar, en dos servicios de maternidad de Río Grande del Sur (Brasil), se reportó una tasa del 51,3 % en un estudio reciente 3 . En Uganda, Pebolo et al 18 reportaron una prevalencia del 73 % (181/249) (IC 95 %: 67-78), mientras que en Etiopía, una revisión sistemática señaló una prevalencia de episiotomía del 42,75 % 19 . En Noruega, datos del hospital universitario de St. Olav's mostraron que aproximadamente el 46,3 % de las mujeres fueron sometidas a episiotomía 20 .…”
Section: Discussionunclassified